Evaluation of institutional models at the ministry of transportation’s railway vocational school in the industrial revolution 4.0 ERA - Nopriyanto, Windi; Handoko, V. Rudy; Maduwinarti, Ayun (Edelweiss Applied Science and Technology, 2025)
PPI Madiun needs to evaluate and optimize its organizational structure to be more adaptive to technological changes and industrial needs in the Industrial Revolution 4.0 era. formulation of the problem in the study. How is the current institutional evaluation of PPI Madiun, what are the obstacles in organizing the PPI Madiun institution? how does the PPI Madiun institutional model adapt to the Industrial Revolution 4.0 theory in research United Nations Development Programme [1] in Sulaiman [2] Qualitative case study research method at PPI Madiun explores institutional adaptation to the Industrial Revolution 4.0 through in-depth analysis. Institutional evaluation at the Indonesian Railway Polytechnic (PPI) Madiun highlights the need for attention to the external context, organizational capacity, stakeholder involvement, learning and adaptation, and institutional transformation to remain relevant in the Industrial Revolution 4.0 era. With the active involvement of stakeholders and the application of continuous learning methods, PPI Madiun can meet the needs of the dynamic railway industry. Various constraints, such as external context and organizational capacity, require a comprehensive strategy, including increased coordination with the government and collaboration with industry. Digital-based transformation and innovative organizational culture will strengthen PPI Madiun as a superior vocational education institution. PPI Madiun’s institutional model that is adaptive to the Industrial Revolution 4.0 focuses on external context, organizational capacity, stakeholder involvement, learning, and institutional transformation to produce a professional workforce.